(untitled) (Kerala Journal of Psychiatry, 2025)
Background: Psychotic features like delusions and hallucinations occur in a clinically meaningful subset of depressive episodes. While Western estimates place the prevalence of psychosis in depression at 15–30%, Indian data are limited. ICD-10 ties psychosis to severe depression, whereas DSM-5 decouples psychosis from severity, and ICD-11 introduces moderate depression with psychotic features. Contemporary, India-specific evidence is needed to inform classification and care. Methods: This cross-sectional study at a tertiary care center evaluated 170 consecutive adult persons with depression (including major depressive episodes in bipolar I/II) who were diagnosed per DSM-5 using SCID-5. Depression and psychosis severity were assessed with the Hamilton Depression Rating Scale (HAM-D) and the Brief Psychiatric Rating Scale (BPRS), respectively. The data were analyzed using ANOVA, the chi-square test, and Pearson’s correlation. Results: Overall, 24.7% (42/170) had psychotic features. Prevalence rose with depression severity: 0% in mild, 8.6% (7/81) in moderate, and 47.9% (35/73) in severe depression, which was significant. (p=0.01) Mean BPRS scores increased across severity strata with significant between-group differences. (F=55.79, p<0.001) HAM-D scores correlated positively with BPRS scores(r= 0.77, p<0.001), indicating that higher depressive severity was associated with greater psychosis severity. Conclusion: Psychotic features occur in approximately one-quarter of persons with major depression and are not confined to severe episodes, with a notable proportion present in moderate depression. The graded increase in both prevalence and severity of psychosis with depressive severity supports DSM-5’s delinking and aligns with ICD-11’s category of moderate depression with psychotic features. These findings underscore the need for routine psychosis screening across all depression severities